Predictive value of neutrophil-to-lymphocyte ratio on hospital outcomes of patients with community-acquired pneumonia - Zakir Hossion; Zabir Hossain; Fatema Islam; Sharmin Yasmin (PLoS ONE, 2026)
Background Community-acquired pneumonia (CAP) remains a leading cause of hospitalization and mortality worldwide, particularly in low- and middle-income countries. Risk stratification is essential for guiding treatment decisions, yet commonly used biomarkers such as C-reactive protein and procalcitonin are costly and not always readily available. The neutrophil-to-lymphocyte ratio (NLR), a simple index derived from routine blood counts, has been proposed as a cost-effective prognostic marker. This study aimed to evaluate the predictive value of NLR on hospital outcomes in patients with CAP. Methods A prospective observational study was conducted in the Department of Medicine at Dhaka Medical College Hospital, Bangladesh, between July 2023 and June 2024. One hundred adult patients with CAP were enrolled using purposive sampling. Demographic, clinical, and laboratory data were recorded at admission, including complete blood counts and CURB-65 scores. NLR was calculated, with ≥7.12 defined as elevated. Patients were followed for outcomes including mortality, oxygen requirement, ICU admission, and length of hospital stay. Statistical analyses included chi-square tests, logistic regression, and ROC curve analysis. Results The mean age of participants was 53.7 ± 10.9 years, and 62% were male. An elevated NLR (≥7.12) was present in 67% of patients and was significantly associated with mortality (p = 0.027), oxygen requirement (p < 0.001), ICU admission (p < 0.005), and prolonged hospital stay (p < 0.001). Regression analysis confirmed NLR ≥ 7.12 is associated with prolonged stay (OR: 15.235; 95% CI: 4.613–50.316; p < 0.001), oxygen requirement (OR: 1.846; 95% CI: 1.415–2.408; p < 0.001), ICU transfer (OR: 5.172; 95% CI: 1.289–20.747; p < 0.001), and mortality (OR: 7.704; 95% CI: 1.962–61.690). ROC analysis showed moderate discriminatory ability for prolonged stay (AUC: 0.762) and modest predictive performance for oxygen need, ICU admission, and mortality. Conclusion Elevated NLR is strongly associated with adverse outcomes in CAP, including mortality, ICU admission, oxygen requirement, and prolonged hospitalization. Given its simplicity and accessibility, NLR may serve as a valuable tool for early risk stratification in resource-limited settings.